Changes in Content of Bioactive Compounds and Antioxidant Activity Induced in Needles of Different Half-Sib Families of Norway Spruce (Picea abies (L.) H. Karst) by Seed Treatment with Cold Plasma - Vaida Sirgedaitė-Šėžienė; Ieva Lučinskaitė; Vida Mildažienė; Anatolii Ivankov; Kazunori Koga; Masaharu Shiratani; Kristina Laužikė; Virgilijus Baliuckas (MDPI AG, 2022)
In order to ensure sufficient food resources for a constantly growing human population, new technologies (e.g., cold plasma technologies) are being developed for increasing the germination and seedling growth without negative effects on the environment. Pinaceae species are considered a natural source of antioxidant compounds and are valued for their pharmaceutical and nutraceutical properties. In this study, the seeds of seven different Norway spruce half-sib families were processed for one or two minutes with cold plasma (CP) using dielectric barrier discharge (DBD) plasma equipment. At the end of the second vegetation season, the total flavonoid content (TFC), DPPH (2,2- diphenyl-1-picryl-hydrazyl-hydrate), and ABTS (2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid)) antioxidant activity, and the amounts of six organic acids (folic, malic, citric, oxalic, succinic, and ascorbic) were determined in the needles of different half-sib families of Norway spruce seedlings. The results show that the TFC, antioxidant activity, and amounts of organic acids in the seedling needles depended on both the treatment duration and the genetic family. The strongest positive effect on the TFC was determined in the seedlings of the 477, 599, and 541 half-sib families after seed treatment with CP for 1 min (CP1). The TFC in these families increased from 118.06 mg g−1 to 312.6 mg g−1 compared to the control. Moreover, seed treatment with CP1 resulted in the strongest increase in the antioxidant activity of the needles of the 541 half-sib family seedlings; the antioxidant activity, determined by DPPH and ABTS tests, increased by 30 and 23%, respectively, compared to the control. The obtained results indicate that the CP effect on the amount of organic acids in the needles was dependent on the half-sib family. It was determined that treatment with CP1 increased the amount of five organic acids in the needles of the 541 half-sib family seedlings. The presented results show future possibilities for using cold plasma seed treatment in the food and pharmacy industries.